2020
DOI: 10.1108/ecam-10-2019-0539
|View full text |Cite
|
Sign up to set email alerts
|

Internal relationships of market-oriented EFQM enablers in the Chinese construction industry

Abstract: PurposeService-oriented innovation economies are becoming the new trend for the construction industry. Benchmarking the quality management level of developed countries and improving quality management are also becoming necessities for promoting innovation in the economy. The purpose of this study is to analyse the internal relationships between the five enablers of the European Foundation for Quality Management (EFQM) Excellence model, based on a market-oriented strategy, to serve as a framework for managing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Kohli and Jaworski (1990) introduced a measure of market orientation from a behavioral and process perspective, suggesting it incorporated; data collection, information transfer, and compilation and conduction of responsive actions. Zhang et al (2020) found that these two scales of market orientation were reliable in a developing country context. They assessed customer orientation, data collection, coordination, and information implementation rationality and application of the scale.…”
Section: Internal Marketing and Market Orientationmentioning
confidence: 89%
See 2 more Smart Citations
“…Kohli and Jaworski (1990) introduced a measure of market orientation from a behavioral and process perspective, suggesting it incorporated; data collection, information transfer, and compilation and conduction of responsive actions. Zhang et al (2020) found that these two scales of market orientation were reliable in a developing country context. They assessed customer orientation, data collection, coordination, and information implementation rationality and application of the scale.…”
Section: Internal Marketing and Market Orientationmentioning
confidence: 89%
“…Internal marketing and entrepreneurial orientation With advancements in innovation, organizations must be familiar with how to compete in these dynamic environments (Zhang et al, 2020). Internal marketing highlights marketing activities to employees in the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the dependent variables are identified in Table 1 as the "results". This measure indicates the performance of the mechanism of influence of socially responsible business activities on the socio-economic development of a region, as Zhang et al [46] explain. According to these authors, economic effects are connected to the expansion of the financial basis of regional and local budgets [46], because socially responsible behavior by business leaders stimulates the creation of new jobs, a commodity mass and additional social programs [47].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…This measure indicates the performance of the mechanism of influence of socially responsible business activities on the socio-economic development of a region, as Zhang et al [46] explain. According to these authors, economic effects are connected to the expansion of the financial basis of regional and local budgets [46], because socially responsible behavior by business leaders stimulates the creation of new jobs, a commodity mass and additional social programs [47]. The effect on the environment is mainly seen in terms of maintaining biodiversity, minimizing the production impact on the environment and the proper management of resources used in the production process [37].…”
Section: Dependent Variablesmentioning
confidence: 99%